SCIENTIFIC AND PRACTICAL RECOMMENDATIONS OVER CREATION AND APPLICATION OF MULTIMEDIA PRESENTATIONS AT CHEMISTRY LESSONS - Maria D. Tukalo (Інформаційні технології і засоби навчання, 2010)
The article allows to determine the methodical expedience and criteria at creation of multimedia educational presentations and specifies the methodological approaches of their use during teaching of chemistry at school according to the teacher’s aim; specifies the features of student’s apprehension of the information.